Rate of Perceived Exertion of Potential Avionics Male Students and Proposed Exercises to Decrease Strain - Harridon, Mohd (International Journal of Engineering and Technology, 2018)
As a student in Aviation, particularly in the field of Avionics, one has to actuate real life practical in real life aircraft. In the field of Avionics, the electrical and electronic racks are usually located in confined and constricted spaces in the cargo bay of the aircraft. To actuate works upon these spaces requires the student to crawl and be in physically stressful position for a predetermined period. If the student could not withstand these situations, then their practical workmanship would be poor. Thus, potential student in Avionics should be fit in order to perform well during these practical sessions. This paper collected the Rate of Perceived Exertion (RPE) of high school students that aspire to be Avionics students after graduating from high school. The RPE showed whether these students could withstand or not the practical in Avionics and the results showed that high school students that are fit felt less exertion, thus more likely to perform well in their practical. The results also showed that high school students that are not fit felt more exertion thus more likely to perform poorly in their practical. This paper also laid out proposed physical exercises to decrease the strain or exertion felt.Â Â